Strategic Management of Community-Based Education: The Role of Funding Strategy and Youth Participation in Enhancing Program Effectiveness through NGO Partnerships - Pramaningtyas Sarce Margareth; Ike Kusdyah Rachmawati; Yunus Handoko (Journal of Educational Management Research, 2026)
This study aims to examine the effects of funding strategies and meaningful youth participation on the effectiveness of community empowerment programs, with strategic partnerships serving as a mediating variable within Non-Governmental Organizations (NGOs). A quantitative research design was employed using a survey method. Data were collected through an online questionnaire distributed via Google Forms to leaders of NGOs that are legally registered as foundations and associations. A total of 50 NGOs were selected using purposive and multistage sampling techniques. The collected data were analyzed using path analysis with Smart-PLS version 4.6.1.1. The findings indicate that funding strategy has a significant positive effect on strategic partnerships, whereas meaningful youth participation does not significantly influence strategic partnerships. Strategic partnerships are also found to have no significant effect on the effectiveness of community empowerment programs. Furthermore, funding strategy does not have a significant direct effect on program effectiveness, while meaningful youth participation shows a significant positive effect. The mediation analysis reveals that strategic partnerships do not mediate the relationship between funding strategy and program effectiveness, nor between meaningful youth participation and program effectiveness. These findings imply that the effectiveness of community empowerment programs is more strongly influenced by the substantive involvement of youth than by funding mechanisms or formal partnerships alone. For practitioners and policymakers, the study highlights the importance of designing empowerment programs that prioritize meaningful youth engagement, while ensuring that funding strategies and partnerships are aligned with programmatic goals rather than treated as stand-alone managerial instruments.